2006
DOI: 10.1080/13689880600716027
|View full text |Cite
|
Sign up to set email alerts
|

Party Strategy and Media Bias: A Quantitative Analysis of the 2005 UK Election Campaign

Abstract: A BSTRACT This article investigates the current state of press partisanship in the UK. Utilizing content analysis data from the 2005 General Election campaign, recent hypotheses about press dealignment are tested with quantitative methods. Partisan tendencies in reporting are measured in terms of coverage bias , statement bias , and agenda bias . As the governing party, Labour benefits from coverage bias in all papers, while the Liberal Democrats remain marginalized. It can be shown that increasingly ambiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 10 publications
0
45
0
2
Order By: Relevance
“…However, some scholars also analyzed the similarity between party agendas and reported party agendas in media coverage -so far producing mixed evidence. In a study on the UK general elections of 2005, Brandenburg found that parties' agendas correlate quite high with parties' agendas reported in the media (Brandenburg, 2006). Similarly, a study analyzing press releases and news coverage at the 2007 Danish parliamentary elections found parties to be differently successful in getting their messages in the news (Hopmann et al, 2010 Helbling and Tresch (2011) found no connection between parties' issue emphasis in electoral programs and in the respective news coverage on the issue of European integration.…”
Section: Theory Election News Coverage and The Role Of Party-issue LImentioning
confidence: 99%
“…However, some scholars also analyzed the similarity between party agendas and reported party agendas in media coverage -so far producing mixed evidence. In a study on the UK general elections of 2005, Brandenburg found that parties' agendas correlate quite high with parties' agendas reported in the media (Brandenburg, 2006). Similarly, a study analyzing press releases and news coverage at the 2007 Danish parliamentary elections found parties to be differently successful in getting their messages in the news (Hopmann et al, 2010 Helbling and Tresch (2011) found no connection between parties' issue emphasis in electoral programs and in the respective news coverage on the issue of European integration.…”
Section: Theory Election News Coverage and The Role Of Party-issue LImentioning
confidence: 99%
“…Previous research has considered party issue agenda-setting in the media (Brandenburg, 2002(Brandenburg, , 2006Hopmann et al, 2012) or the visibility of political actors in the news (Cook, 1988;Gattermann & Vasilopoulou, 2015;Kriesi, 2012;Tresch, 2009). More recent studies have focused on media gatekeeping of individual messages such as parliamentary questions (Van Aelst & Vliegenthart, 2014;Van Santen et al, 2015) and party pledges (Kostadinova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dissemination: There is an extensive compendium of research on bias in the dissemination of news in print, radio, and television. A small sample of the research includes studies on bias in photographs in newspapers and news magazines [5,42,55,76,77], research into the overarching area of visual biases [38,43,56,96], bias in news anchors' facial expressions [32,73,80,117], news anchor intonation and tone [41,78], presenters' non-verbal communication [3,69,114], television soundbites and image-bites [24,40], newspaper layout [8,99], newspaper coverage [9,10,17,58,59,64,84,92], newspaper headlines and lead stories [105,52,58,60,63,70,98,106,108,110], and description or labelling bias [22,66,67,68].…”
Section: Motivationmentioning
confidence: 99%